A New Fourth-Order Embedded Method Based on the Harmonic Mean (MATEMATIKA, 1998)
In this paper we formulate an embedded method based on harmonic and arithmetic means of order 4. This method together with RK-Harmonic scheme may be used to estimate the solutions of initial value problems. The absolute stability region of this scheme is also studied and we conclude with a numerical example to justify the effectiveness of the method. Keywords: Harmonic Mean; Runge-Kutta method; stability; error control. Dalam kertas ini kami rumuskan satu kaedah terbenam berperingkat 4 yang berasaskan min harmonik dan min aritmetik. Kaedah ini berserta de\-ngan skema RK-Harmonik boleh digunakan bagi menganggarkan penyelesaian kepada masalah nilai awal. Rantau kestabilan untuk skema ini juga dikaji dan kita simpulkan dapatan ini dengan satu contoh masalah sebagai mengesahkan keberkesanan kaedah ini. Katakunci: Min-Harmonik; Kaedah Runge-Kutta; kestabilan; kawalan ralat.